The identification of the polypeptides of NADPH-protochlorophyllide oxidoreductase - Oliver, Richard; Griffiths, W. (1980)
The peptides of protochlorophyllide reductase have been identified by a covalent-radioactive labelling technique. This produced two labelled peptides of mol.wts. 35000 and 37000.